Morphological and histological studies of brain development in embryos and larvae of the common carp Cyprinus carpio (L. 1758) - Mojer, A.M.; Mezyad , Z.A.K.; Saleh, J.H. (Mesopotamian Journal of Marine Sciences, 2022)
In the present study, the morph-histological characterization of the brain development in common carp was studied in Basrah, Southern Iraq, by examining the several samples of eggs and larvae of Common carp Cyprinus carpio. The temperature of the water in incubators was 25 -27 ˚C and the incubation of eggs were carried out for 38 hour. Morphologically, neural stage was emerged after eight hours of incubation with continuation of epiboly processes Brain was progressively differentiated into three main parts namely forebrain, midbrain and hindbrain. Forebrain was differentiated into telencephalon and diencephalon. Optic primordial was appeared after 12 hours of fertilization in a form of evagination from both sides of the forebrain and slightly oval elongated and then characterized optic vesicle, then the lens was appeared. Hindbrain was clearly differentiated and neuromerse was marked after 22 hours of fertilization. Histologically, the brain at the age of 24 hours was composed of a mass of undifferentiated neuroectoderm, whilst at the age of 28 hours appeared more differentiated with clarity a cerebral hemisphere on both sides of the forebrain and it was a mass of undifferentiated neuron cells. Gradually, the brain parts were completed with a differentiation of several layers until the age of 20 days after hatching.